2010 IEEE International Conference on Software Maintenance 2010
DOI: 10.1109/icsm.2010.5609735
|View full text |Cite
|
Sign up to set email alerts
|

Enabling multi-tenancy: An industrial experience report

Abstract: Abstract-Multi-tenancy is a relatively new software architecture principle in the realm of the Software as a Service (SaaS) business model. It allows to make full use of the economy of scale, as multiple customers -"tenants" -share the same application and database instance. All the while, the tenants enjoy a highly configurable application, making it appear that the application is deployed on a dedicated server. The major benefits of multi-tenancy are increased utilization of hardware resources and improved e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 14 publications
(20 reference statements)
0
58
0
8
Order By: Relevance
“…This single instance serves all customers at the same time (multi-tenancy [3]). Implementing and rolling out new features in a SaaS environment is at the same time promising (as rollouts are entirely under the control of the service provider) and challenging (as every rollout potentially impacts each customer) [4]. Further, the SaaS model gives service providers ready access to a rich set of live performance and usage data, including, for instance, clickstream data, fault logs, accurate production performance metrics, or even production user data (e.g., uploaded videos, number and type of Skype contacts).…”
Section: Vendor Vendor Vendormentioning
confidence: 99%
See 1 more Smart Citation
“…This single instance serves all customers at the same time (multi-tenancy [3]). Implementing and rolling out new features in a SaaS environment is at the same time promising (as rollouts are entirely under the control of the service provider) and challenging (as every rollout potentially impacts each customer) [4]. Further, the SaaS model gives service providers ready access to a rich set of live performance and usage data, including, for instance, clickstream data, fault logs, accurate production performance metrics, or even production user data (e.g., uploaded videos, number and type of Skype contacts).…”
Section: Vendor Vendor Vendormentioning
confidence: 99%
“…Further, software developers typically are able to further refine feedback specifications during visualization (e.g., via a slider in the IDE which controls the granularity of feedback that is visualized). Feedback control encompasses five steps, (1) data collection, (2) data filtering, (3) data aggregation, (4) data 4 http://aws.amazon.com/cloudwatch/ integration, and (5) feedback mapping, as depicted in Figure 5. Figure 4.…”
Section: Feedback Controlmentioning
confidence: 99%
“…In the SaaS context, configuration is aimed to provide each tenant with multitude of options and variations without changing the SaaS application source code and this modification should done by the tenant at run-time without suspend the application during the configuration [11], [21], [37]. With the multi-tenant architecture, some researchers found that the customization must be made possible only through the configuration [15], [38].…”
Section: Configuration and Customizationmentioning
confidence: 99%
“…These benefits result in lower maintenance costs that allow the provider to target also small and medium-size enterprises and thus to catch the "long tail" of the market. [2], [15], [16] On the other hand, there are also disadvantages of multitenancy. Since the tenants share hardware resources, a problem caused by one of the tenants have an impact also on other tenants.…”
Section: A Cloud Computing and Saas Architecturementioning
confidence: 99%
“…In a multitenant architecture, a single instance of common code and data is shared between multiple tenants [15]. Besides the requirements of shared hardware resources, shared application and shared database instance, Bezemer et al requires also high degree of configurability in look-and-feel and workflow from multitenant software [16]. Some researchers consider also multi-instancy as a form of multitenancy [14], where vendors host separate instances for each customer within shared hardware [13], [14].…”
Section: A Cloud Computing and Saas Architecturementioning
confidence: 99%